Analysis of environmental driving factors on Core Functional Community during Daqu fermentation. (July 2022) - Zhu, Qi; Chen, Liangqiang; Peng, Zheng; Zhang, Qiaoling; Huang, Wanqiu; Yang, Fan; Du, Guocheng; Zhang, Juan; Wang, Li
Graphical abstract: Highlights: The Core Functional Community (CFC) were composed of Daqu 7 bacterial and 4 fungal genera which can both produce key enzymes and flavor substances. High temperature and acidity were significant driving factors which made CFC composed of heat-resistant microorganisms. The bacterial function genera contributed more to the formation of significant flavors than fungi. High temperature helps the formation of Tetramethylpyrazine, 2-Furancarboxaldehyde and 2-Furanmethanol. Abstract: Sauce-flavor Daqu determines the quality of Baijiu because its core functional community (CFC) can produce abundant enzymes and aroma. However, complex environmental factors make it difficult to accurately control the fermentation quality of Daqu . In this study, we constructed a functional gene database to identify CFC based on multi-omics technology and explore controllable environmental factors of CFC to improve the quality of Daqu . The results showed that the CFC is mainly composed of 7 bacterial and 4 fungal genera, including Kroppenstedtia, Thermoactinomyces, Bacillus, Acinetobacter, Brevibacterium, Saccharopolyspora, Ochrobactrum, Aspergillus, Byssochlamys, Thermoascus, and Thermomyces . Most of them are thermostable microorganisms that can provide the power of fermentation and saccharification (α-amylase, glucoamylase, and protease). In CFC, Acinetobacter and Saccharopolyspora were strongly positively correlated with typical flavor substances, while fungi were negatively correlated, particularly with furans. Therefore, the bacterial genera contributed more to the significant flavors. The CFC was significantly influenced by high temperature and total titrate acid based on RDA. In addition, high-temperature conditions were also strongly positively correlated with flavors that can be quickly produced at high temperatures, such as 2-Furancarboxaldehyde, 2-Furanmethanol, and Tetramethylpyrazine. As a controllable factor, the temperature can be adjusted to improve the quality of Daqu directionally, which will provide theoretical guidance for the production of high-quality Daqu .